Effect of routine first‐trimester combined screening for pre‐eclampsia on small‐for‐gestational‐age birth: secondary interrupted time series analysis. (5th January 2022) - Guy, G. P.; Leslie, K.; Diaz Gomez, D.; Forenc, K.; Buck, E.; Bhide, A.; Thilaganathan, B.
ABSTRACT: Objective: To evaluate the impact of a first‐trimester combined screening program for pre‐eclampsia, based on the Fetal Medicine Foundation (FMF) algorithm, on the rate of small‐for‐gestational age (SGA) at birth and adverse pregnancy outcome. Methods: This was a retrospective cohort study of data obtained from a London tertiary hospital between January 2017 and March 2019. The data were derived from a secondary analysis of the cohort evaluated in a clinical‐effectiveness study on the implementation of a first‐trimester screening program for pre‐eclampsia. The cohort included 7720 women screened according to the UK National Institute for Health and Care Excellence (NICE) risk‐based approach and 4841 women screened by the FMF multimodal approach, which combines maternal risk factors, blood pressure, pregnancy‐associated plasma protein‐A and uterine artery Doppler indices. The care package for the FMF‐screened group included 150‐mg aspirin prophylaxis, ultrasound scans at 28 and 36 weeks' gestation and scheduled delivery at 40 weeks. Outcome measures included the rates of SGA neonates at birth, admission to the neonatal unit, intrauterine demise, neonatal death and hypoxic–ischemic encephalopathy assessed by interrupted time series analysis (ITSA). Results: There was no significant difference in the rates of intrauterine demise, neonatal death and hypoxic–ischemic encephalopathy between the FMF‐screened and NICE‐screened cohorts. ITSA showed a significant reduction in the rate of term SGA birth < 10 th percentile at 21 months following implementation of the FMF screening program, with a relative effect reduction of 45.1% ( P  = 0.004). However, there was no significant relative effect reduction in term SGA birth < 5 th or < 3 rd percentile. Conclusions: First‐trimester combined screening for pre‐eclampsia based on the FMF algorithm accompanied by a care package including serial ultrasound scans for growth evaluation and elective birth from 40 weeks' gestation resulted in a significant 45% relative effect reduction in term SGA birth < 10 th percentile but did not affect term SGA birth < 5 th or < 3 rd percentile. Further screening strategies to detect and improve the outcome of cases with SGA birth < 5 th percentile need to be considered. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.